Legality of Land Ownership by Non-native Indonesian Citizens in Yogyakarta Through Nominee Agreement (Case of Decision Number 443 PK/PDT/2023) - Prasida Alya Putri (The Digest: Journal of Jurisprudence and Legisprudence, 2026)
Special Region of Yogyakarta is one of the regions in Indonesia that possesses special authority in administering its local governance, including matters related to land regulation. Based on the Instruction of the Deputy Governor No. K.898/I/A/1975 concerning the Provision of Handling Rights of Land and Buildings, Indonesian citizens who are not categorized as natives of the region are prohibited from holding land under ownership rights. In practice, this regulation has created opportunities for the use of nominee agreements between Non-native Indonesian citizens and native citizens to circumvent restrictions on land ownership. Therefore, this research aims to examine the legality of land ownership through nominee agreement used by Non-native Indonesian citizens based on Supreme Court Decision Number: 443 PK/Pdt/2023 and to analyze the legal implications arising from the application of such agreements in acquiring ownership rights over land. This research employs a normative juridical method with both case and statute approaches. The data used consist of secondary sources, including primary legal materials such as court decisions and legislation, as well as secondary legal materials in the form of books, journals, and legal articles. The results indicate that the use of nominee agreements by Non-native Indonesian citizens to obtain ownership rights over land in the region lacks a valid legal basis within the Indonesian land law system and is regarded as a form of legal circumvention that is juridically invalid.